LA "GONFOLITE LOMBARDA": STRATIGRAFIA E SIGNIFICATO NELL'EVOLUZIONE DEL MARGINE SUDALPINO (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
The Oligocene-Miocene succession of the "Gonfolite Lombarda" outcrops in Western Lombardy and is largely represented in the subsurface of the northern PO Plain. In the this group was considered as a typical example of post- orogenic molasse deposit. The new data suggest that it represents a clastic wedge infilling a deep foreland basin flanking a zone of continental collision. The stratigraphic evolution of the succession strictly reflects the tectono-sedimentary evolution of the basin.The succession (almost 3000 m thick) between Como and Varese covers a time span from late early Oligocene (late Rupelian) at least to early Miocene (Burdigalian). It consists of clastic sediments deposited in a deep-sea environment. Both the benthic Foraminifera and the macrofossil assemblages indicate that these sediments were deposited in the epibathial zone (from 500-700 m to 1000-1300 m) throughout all the time span considered. The succession can be splitted in two main segments based on their different sedimentary characters and because they are separated by a regional unconformity corresponding to a hiatus of several million years. The lower one is represented by the Chiasso Formation (about 170m thick) and the upper one by the Gonfolite Group s. Str. (about 2800 m thick).The Chiasso Formation is a depositional sequence late Oligocene (late Rupelian to early Chattian) in age. It consists of mudstones and rare thin-bedded turbidites, representing slope or slope-base deposits. The overlying Gonfolite Group represents the build-up of several deep sea fan systems one on top of the other during the very late Oligocene (late Chattian) to the early Miocene (Aquitanian- Burdigalian) and perhaps to the middle Miocene. Resedimented conglomerates infilled deeply incised canyons confined by natural levees in their distal part. The canyons evolved laterally and distally to still partly confined sandy depositional lobes during the early Miocene.In the Gonfolite Group three depositional sequences could be recognized. The first one is represented by the Como Conglomerate (800-1500 m thick) and of some heteropic formations, covering a time span from late Chattian to early Burdigalian. This depositional sequence represents an asymmetric megacycle with an initillly very rapid progradation of the conglomeratic system followed by its gradual regression and, in the Como area, by a westward shift of the system axis. Moreover, it is worth mentioning that pebbles of granodiorite-diorite called "ghiandone and serizzo" of the Val Masin0-Val Bregaglia Massif make their appearance already in the basal part of the Como Conglomerate.The second depositional sequence consists of the Lucino Conglomerate (800-1000 m thick) and of some heteropic formations. It represents a gradual progradation of the whole deep sea fan system during the late earIy Miocene (Burdigalian).In the Varese area, the Gurone Sandstone (120 m thick) may represent a third depositional sequence, which because of its stratigraphic position is younger than the late Burdigalian, and it appears to be deposited prior to the late Miocene (Tortonian).The "Gonfolite Lombarda" basin was interested by an intense and continue tectonic activity with at least two periods of "crisis" occurring in the late Chattian and in the early Burdigalian. Because of the strong tectonic Control it's difficult to correlate the "Gonfolite Lombarda" depositional sequences with the generalized sea level curves.
Keywords: Stratigraphy; Palaeogeography; Oligo-Miocene; Southern Alps.